2018
DOI: 10.1002/1873-3468.13219
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature Raman spectroscopy reveals small chromophore distortion in primary photointermediate of proteorhodopsin

Abstract: Proteorhodopsin (PR) is a microbial rhodopsin functioning as a light-driven proton pump in aquatic bacteria. We performed low-temperature Raman measurements of PR to obtain the structure of the primary photoproduct, the K intermediate (PR ). PR showed the hydrogen-out-of-plane modes that are much less intense than those of bacteriorhodopsin as the prototypical light-driven proton pump from haloarchaea. The present results reveal the significantly relaxed chromophore structure in PR , which can be coupled to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…For p HR K , the CC stretching and CH in-plane bending modes exhibit different spectral features from those of p HR hypso and the dark state, which is caused by the isomerization of the chromophore. The intensity patterns of the vibrational bands, including the single-band appearance of the CC stretching modes (∼1200 cm –1 ), were commonly observed in the K intermediate of BR , and proteorhodopsin with the proton-pump activity, and were attributed to the 13- cis form of their retinal chromophores. Importantly, the spectrum of p HR K is characterized by intense HOOP modes.…”
Section: Resultsmentioning
confidence: 98%
“…For p HR K , the CC stretching and CH in-plane bending modes exhibit different spectral features from those of p HR hypso and the dark state, which is caused by the isomerization of the chromophore. The intensity patterns of the vibrational bands, including the single-band appearance of the CC stretching modes (∼1200 cm –1 ), were commonly observed in the K intermediate of BR , and proteorhodopsin with the proton-pump activity, and were attributed to the 13- cis form of their retinal chromophores. Importantly, the spectrum of p HR K is characterized by intense HOOP modes.…”
Section: Resultsmentioning
confidence: 98%
“…10-100-fold slower) decay of K compared with that of BR was observed in GPR [105]. Because of such slow K-decay, low-temperature Raman spectroscopic data presented by Fujisawa et al demonstrated that the chromophore structure in GPR in the K state is less distorted compared to that of BR in the same state and is rather close to that of L in BR, which possess a more relaxed chromophore structure [112]. Therefore, the formation of a longer stable K state may obscure the appearance of L in the GPR along with the fast formation of the following M-state.…”
Section: Photocycles Of Other H + -Pumping Rhodopsins Than Brmentioning
confidence: 99%
“…A recent Raman study of PR showed that the structure of the RSB chromophore was insensitive to the protonation state of the aspartate near the Schiff base. 8 A small distortion about the Schiff base was also revealed for the initial photointermediate of PR produced at 80K. 8 These observations were attributed to the loose binding site around the Schiff base.…”
mentioning
confidence: 97%